Increased susceptibility to oxidative stress‐ and ultraviolet A‐induced apoptosis in fibroblasts in atypical progeroid syndrome/atypical Werner syndrome with LMNA mutation. (August 2016) - Motegi, Sei‐ichiro; Uchiyama, Akihiko; Yamada, Kazuya; Ogino, Sachiko; Yokoyama, Yoko; Perera, Buddhini; Takeuchi, Yuko; Ishikawa, Osamu
Abstract: Atypical progeroid syndrome (APS), including atypical Werner syndrome (AWS), is a disorder of premature ageing caused by mutation of the lamin A gene, the same causal gene involved in Hutchinson‐Gilford syndrome (HGS). We previously reported the first Japanese case of APS/AWS with a LMNA mutation (p.D300N). Recently, it has been reported that UVA induced abnormal truncated form of lamin A, called progerin, as well as HGS‐like abnormal nuclear structures in normal human fibroblasts, being more frequent in the elderly, suggesting that lamin A may be involved in the regulation of photoageing. The objective of this study was to elucidate the sensitivity to cell damage induced by oxidative stress or UVA in fibroblasts from APS/AWS patient. Using immunofluorescence staining and flow cytometry analysis, the amount of early apoptotic cells and degree of intra‐cellular reactive oxygen species (ROS) generation were higher in H2 02 ‐ or UVA‐treated APS/AWS fibroblasts than in normal fibroblasts, suggesting that repeated UV exposure may induce premature ageing of the skin in APS/AWS patients and that protecting against sunlight is possibly important for delaying the emergence of APS/AWS symptoms. In addition, we demonstrated that H2 O2 ‐, or UVA‐induced apoptosis and necrosis in normal and APS/AWS fibroblasts were enhanced by farnesyltransferase inhibitor (FTI) treatment, indicating that FTI might not be useful for treating our APS/AWS patient.